Organizational Culture and Implementation of Electronic Project Monitoring Information System in Public Tertiary Institutions in Kenya - Mburugu, Kirema N.; Mulwa, Angeline S.; Kyalo, Dorothy N. (My University, 2017)
This article highlights the influence of organisational culture on implementation of electronic project monitoring information system (e-ProMIS) in public tertiary institutions. It is based on literature review and field research by employing cross sectional descriptive survey and correlational research design. Data was collected using questionnaire from 30 tertiary institutions and a sample size of 162 members of staff selected through stratified random sampling technique. To ensure validity and reliability of the questionnaire, pretesting was conducted. Data was analysed using both descriptive and inferential statistics. The study findings indicated that majority of the Tertiary institutions in Kenya practiced bureaucratic culture followed by innovative culture then supportive culture. Correlational results using Pearson’s Product Moment Technique indicated positive and significant coefficients between the indicators of organisational culture and implementation of e-ProMIS in the public tertiary institutions in Kenya. The test of hypothesis showed a statistically significant relationship between organisational culture and implementation of electronic project monitoring information system in public tertiary institutions in Kenya. Based on the research findings the null hypothesis that organisational culture has no significant influence on the implementation of Electronic Project Monitoring Information System in Public Tertiary Institutions in Kenya was rejected and it was conclude that organisational culture has a statistically significant influence on the implementation of Electronic Project Monitoring Information System in Public Tertiary Institutions in Kenya. These study findings imply that for successful implementation of e-ProMIS and other egovernment systems, organisational culture is imperative.
Keywords: organisational culture; implementation; electronic project monitoring information system; tertiary institutions